Effect of edible oil on the quality of beef in short-term preservation - Mahmud, S; Hasan, MM; Akhter, S; Hashem, MA; Rahman, MM (Meat Research, 2024)
This study evaluated the influence of olive, mustard, sesame, and soybean oils on the quality and preservation of raw beef stored at 4±1ºC. Meat was divided into five groups: T0 (control), T1 (olive), T2 (mustard), T3 (sesame), and T4 (soybean), with assessments on days 0, 3, 6, and 9 for physicochemical, oxidative, microbial, and sensory parameters. Oil treatments significantly impacted meat properties (P<0.05). pH levels were lowest in T4 (soybean), while the control increased from 5.23 to 6.88 after 9 days (P<0.01). Water-holding capacity (WHC) was highest in T3 (sesame) (93.29–94.40%), and drip loss was lowest in T1 (olive) (P<0.001). Cooking loss was most favorable in T3 (26.62–27.71%). Color values were best in T3 , with L* (42.06), a* (16.81), and b* (10.52) (P<0.01). TBARS values were lowest in T1 (0.20–0.56), indicating superior oxidative stability (P<0.01). Proximate composition showed T2 (mustard) had the lowest dry matter (25.96–27.03%), T1 had the highest crude protein (21.74%) and the lowest ether extract (2.47–2.65%). Ash content increased with storage, with T4 showing the highest values (1.27– 1.36%). Oil-treated samples had lower microbial counts (P<0.05). TVC ranged from 5.33 to 5.52 log10 CFU/g, with T1 being the lowest. T1 also had the lowest total coliform count (2.44–2.90 log10 CFU/g), while T2 had the lowest yeast-mold count (2.48–2.87 log10 CFU/g). Overall, olive oil (T1 ) was most effective in prolonging shelf life, reducing lipid oxidation, and microbial proliferation. Sesame oil (T3 ) improved color, WHC, and cooking yield. Mustard oil (T2 ) contributed to dry matter content and antimicrobial effects, while soybean oil (T4 ) supported ash content and pH stability. Oil incorporation improves meat quality, shelf life, and consumer acceptability.